Certain subclass of close-to-convex univalent functions defined with q-derivative operator - SINGH, Gagandeep; SINGH, Gurcharanjit (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
The objective of this paper is to introduce a new subclass of strongly close-to-convex functions defined with q-derivative operator and by subordinating to generalized Janowski function. We establish several useful properties such as coefficient estimates, distortion theorem, argument theorem, inclusion relations and radius of convexity for this class. Some relevant connections of the results investigated here with those derived earlier are mentioned. Mathematics Subject Classification (2010): 30C45, 30C50. Received 10 December 2024; Accepted 01 April 2025.